Produção de ovos de poedeiras das raças Plymouth rock barrada, Plymouth rock branca e Rhode island red - Ferreira, Priscila Becker (2013)
This work was done with the database of layers of brown-shelled eggs of Barred Plymouth Rock (BPR), White Plymouth Rock (WPR) and Rhode Island Red (RIR) breeds, for the years 1998 and 2010, created the Laboratory of Poultry Science (LAVIC) of Department of Animal Science, in the Federal University of Santa Maria (UFSM). In chapter 1 aimed to identify the mathematical model (linear or nonlinear) that best describes the curve of egg production of laying hens BPR, WPR and RIR; verify that a single equation can be used to describe the production of eggs different breeds through the test model identity and equal parameters, to study the biological interpretation of the parameters estimated by the models by correlations between parameters and egg production in different weeks old. The study indicated that the quartic polynomial regression and nonlinear models Quadratic Logarithm and Logistics II can be used to estimate the curve of egg production of birds BPR, WPR and RIR. The curves of egg production estimates by race are different, and egg production of breed WPR higher. A single curve of egg production estimated to be 1998 to 2010 birds WPR. The persistence of posture is similar among poultry breeds BPR and WPR. The potential maximum weekly posture of birds breed BPR is intermediate, and can be of the same birds WPR breed or RIR breed. Data productive of the 27th, 38th and 40th at 50 weeks of age can be used as partial data to estimate the curve of egg production, because they are correlated with the maximum potential posture weekly, and the rate of decline, which are highly correlated with the 1st principal component. In chapter 2 was to verify the existence of phenotypic divergence between layers of WPR and BPR through multivariate analysis (multivariate analysis of variance, principal components and clustering) of egg production weekly and accumulated periods. It is concluded that the egg production of poultry breeds BPR and WPR is different. The first two principal components meet the total variation of egg production accumulated the 21st to 25th, 21st to 30th, 21st to 40th, 21st to 45th, and 21st to 50th. Most of the phenotypic variation of the layers can be explained by the cumulative egg production of the 21st until the 40th week of age (10 months), and this variable is highly correlated with total egg production. Families from the race WPR and BPR form seven distinct groups, but homogeneous by the similarity between them. This allows direct crossings between different groups in search of heterosis. In chapter 3 aimed to define the mixed model that best fits the observed data of egg production of laying hens from 5th to 12th month of age, test different structures of the matrices G and R and to estimate broad-sense heritability and correlations environmental and genotype. This study indicated that the random regression model using regression of first grade and structures of (co)variance matrix for UN random effects (G) and UNR for waste matrix (R) models adequately curve of egg production from BPR and WPR laying hens. From the eighth month value heritability is moderate (0.34) with high genotypic correlation estimates (0.78 to 0.97) with nine months, 10, 11 and 12. It is also a high correlation of genotypic values of hens for egg production of the 8th month in the final months of posture. Thus, it is suggested phenotypic selection from the 8th month of production for birds BPR and WPR.